2014
DOI: 10.1016/j.taap.2014.10.009
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive evaluation of the efficacy of leading oxime therapies in guinea pigs exposed to organophosphorus chemical warfare agents or pesticides

Abstract: The currently fielded pre-hospital therapeutic regimen for the treatment of organophosphorus (OP) poisoning in the United States (U.S.) is the administration of atropine in combination with an oxime antidote (2-PAM Cl) to reactivate inhibited acetylcholinesterase (AChE). Depending on clinical symptoms, an anticonvulsant, e.g., diazepam, may also be administered. Unfortunately, 2-PAM Cl does not offer sufficient protection across the range of OP threat agents, and there is some question as to whether it is the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
37
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 58 publications
3
37
1
Order By: Relevance
“…Interestingly, while this same oxime completely prevented lethality against both percutaneously (Snider et al, 2015) or subcutaneously (Wilhelm et al, 2014) administered VX, it did not significantly promote overall survival against PHO in either previous reports. Efficacy in those studies was evaluated at 24-hr after a LD 85 challenge followed by a single administration of therapy that was given either 1 min or at onset of clinical toxic signs.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Interestingly, while this same oxime completely prevented lethality against both percutaneously (Snider et al, 2015) or subcutaneously (Wilhelm et al, 2014) administered VX, it did not significantly promote overall survival against PHO in either previous reports. Efficacy in those studies was evaluated at 24-hr after a LD 85 challenge followed by a single administration of therapy that was given either 1 min or at onset of clinical toxic signs.…”
Section: Discussionmentioning
confidence: 55%
“…Although the mechanism of toxicosis via cholinolergic hyperstimulation is the same between OP insecticides/pesticides and OP CWNAs, the relative potencies can be radically different. In general, CWNAs such as sarin, soman, cyclosarin, VX and Russian VX (VR), have been shown to exhibit greater toxicity than bioactivated OP pesticides such as paraoxon, chlorpyrifos-oxon and phorate oxon or PHO (Balali-Mood and Shariat, 1998;Wilhelm et al, 2014;Snider et al, 2015;Misik et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Clinical opinions on the value of oximes as adjunct in the treatment of human poisoning with OPC remain divided. While some authors reported disappointing experiences with oximes (Eddleston et al, 2002;Peter et al, 2006), according to other authors, oximes are beneficial if used properly (Jokanovic, 2012;Wilhelm et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, currently available antidotal treatment consisting of atropine and commonly used reactivator of inhibited AChE (pralidoxime, obidoxime, trimedoxime, HI-6) is not able to sufficiently counteract acute toxic effects of tabun because of low ability of oximes to reactivate tabun-inhibited AChE Q3 (Jokanovic and Prostran, 2009;Jokanovic, 2012;Wilhelm et al, 2014). Therefore, the antidotal treatment of acute poisoning with tabun still remains a serious problem and the development of new and more effective AChE reactivator is still very important (Sharma et al, 2015).…”
mentioning
confidence: 99%
“…Current treatment relies on the use of anticholinergic drug atropine to reduce the effects of accumulating acetylcholine usually combined with oximes that reactivate phosphylated AChE (3)(4)(5). However, the potential of the oximes used in medical practice today, such as 2-PAM, HI-6, and obidoxime, is limited primarily due to the very specific properties of each of the enzyme-OP conjugates (6)(7)(8)(9).…”
mentioning
confidence: 99%